Índice de preços do subitem transporte aéreo no Brasil - Vasconcelos, Leonardo Siqueira (2017)
The availability of online prices represents a unique opportunity for the construction of price indexes and the measurement of inflation. This type of data can be collected remotely, at much higher frequencies, and a tiny fraction of the cost of traditional price- collection methods. The Brazilian Institute of Geography and Statistics (IBGE), through the Broad National Consumer Price Index (IPCA), already collects data online for the subitem airfare. The paper seeks to show evidence that simple collection on company websites is not always the best way to obtain price variations due to automatic price swings. Additionally, a review of the theoretical and empirical literature highlighting the national and international collection method is presented. In order to reach the proposed objective, we used the time-series econometric procedure using the Vector Autoregressive Model related to the National Civil Aviation Agency (ANAC) price changes.